Metabolic cost of horticulture activities in older adults - Park, Sin-Ae; Lee, Kwan-Suk; Son, Ki-Cheol; Shoemaker, Candice A. (My University, 2012)
The exercise intensity of three different horticulture activities (propagating herbs, transplanting, and making a vegetable garden) in older adults was determined. Seventeen older Korean adults (mean age 66.9 ± 2.7 years, body mass index 26.8 ± 3.4) that met the inclusion criteria (over 65 years in age, no uncontrolled chronic diseases, no heart and lung diseases, no pacemaker, and nonsmoking) participated in the study. The subjects visited the Konkuk University campus, Seoul, South Korea two times to complete the horticulture activities during June 2011. Propagating herbs and transplanting were completed in a glasshouse during the first visit, with each activity taking about 20min. The third activity involved making a vegetable garden and required an average of 25 min during the second visit. Metabolic and heart rates during each activity were determined using a portable calorimetric instrument with a radiotelemetry monitor. Propagating herbs and transplanting were determined to be low intensity physical activities (2.4 ± 0.5 metabolic equivalents (METs) and 2.7 ± 0.5METs, respectively) while making a vegetable garden was a moderate intensity physical activity (3.7 ± 0.7METs) for older adults.
Keywords: Energy expenditure; Physical activity; Gardening; Horticultural therapy; Human issues in horticulture